Problems of Prevention of Crimes and other Violations in the Sphere of Labor Relationship of Modern Russia - EPIKHIN, Alexander Yuryevich; MAKEEVA, Inna Vladimirovna; RYZHKOVA, Irina Dmitriyevna (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
The purpose of this study is to identify problems in labor relationship in the Russian Federation. The authors use the term ‘labor fraud’. There is a differentiation from the fraud in general criminal sense. There is a necessity to introduce criminal responsibility for ‘labor frauds’. Similar experience of foreign countries is considered in a positive way. Among main conclusions derived from the work it is to provide the following theses:  The constitutional right of employees to receive compensation for labor is not protected fully. Civil and administrative legal responsibility is not sufficient to realize this right fully;  The solution of the problem on the observance of employees’ rights in full should be based on the achievements of legal science, in particular, science of labor and criminal law;  The actual legal status of the employee provided by the law and its implementation mechanism brings the labor relationship to a new level which positively affects the reputation of the welfare state.
Keywords: labor relationship, employee, employer, compensation for labor, ‘labor fraud’